Microbial communities of a variety of 75 homemade fermented vegetables - Thierry, Anne; Madec, Marie-Noelle; Chuat, Victoria; Bage, Anne-Sophie; Picard, Olivier; Grondin, Cécile; Rué, Olivier; Mariadassou, Mahendra; Marché, Laurent; Valence, Florence (Frontiers in Microbiology, 2023)
Fermentation is an ancient practice of food preservation. Fermented vegetables are popular in Eastern European and Asian countries. They have received a growing interest in Western countries, where they are mainly manufactured at domestic and artisanal scales and poorly characterized. Our aim was to investigate the microbial communities and the safety of French homemade fermented vegetables, in the frame of a citizen science project. Fermented vegetables and the data associated with their manufacture were collected from citizens, and characterized for pH, NaCl concentration, and microbiology by culturomics and 16S DNA metabarcoding analysis. Lactic acid bacteria (LAB) and yeast isolates were identified by 16S rRNA gene sequencing and D1/D2 domains of the large subunit of the rRNA gene, respectively. The 75 collected samples contained 23 types of vegetables, mainly cabbage, followed by carrots and beets, and many mixtures of vegetables. They were 2 weeks to 4 years old and their median pH was 3.56, except two samples with pH over 4.5. LAB represented the dominant viable bacteria. LAB concentrations ranged from non-detectable values to 8.7 log colony-forming units (CFU)/g and only depended on the age of samples, with high most frequently observed in the youngest samples (< 100 days). The 93 LAB isolates identified belonged to 23 species, the two mains being Lactiplantibacillus pentosus/plantarum and Levilactobacillus brevis. The other microbial groups enumerated (total aerobic bacteria, halotolerant bacteria, Gram-negative bacteria, acetic acid bacteria) generally showed lower concentrations compared to LAB concentrations. No pathogenic bacteria were detected. Viable yeasts were observed in nearly half the samples, at concentrations reaching up to 8.0 log CFU/g. The 33 yeast clones identified belonged to 16 species. Bacterial metabarcoding showed that two main orders, Lactobacillales (i.e. LAB, 79% of abundance, 177 of the 398 total ASVs) and Enterobacterales (19% of abundance, 191 ASVs). Fifteen LAB genera were identified, with Lactiplantibacillus and Levilactobacillus as the most abundant, with 41% and 12% of total reads, respectively. Enterobacterales members were mainly represented by Enterobacteriaceae and Yersiniaceae. This study is the first wide description of the microbiota of a large variety of homemade fermented vegetables and documents their safety.